2016
DOI: 10.1017/s0950268816001898
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological investigation of a tap water-mediated hepatitis E virus genotype 4 outbreak in Zhejiang Province, China

Abstract: An outbreak of acute hepatitis recently occurred in a nursing home in Zhejiang Province, China. The objectives of this study were to confirm the outbreak and identify the aetiology, source and transmission patterns. All residents and staff in or near the nursing home during the period from 1 October 2014 to 21 May 2015 were investigated regarding hygiene and for epidemiological information including water and food (eating meat especially pork products). Serum and stool specimens were collected for detection of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 30 publications
(35 reference statements)
0
19
0
Order By: Relevance
“…Six studies were at low risk for all criteria [15][16][17][18][19][20]. Problems related to recall bias and standardization of self-reported measurement created a high risk of bias for the measurement of the exposure domain in seven studies [14,[21][22][23][24][25][26]. Lack of consideration for confounders led to a high risk of bias in four studies [24,[27][28][29].…”
Section: Risk Of Bias In the Included Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Six studies were at low risk for all criteria [15][16][17][18][19][20]. Problems related to recall bias and standardization of self-reported measurement created a high risk of bias for the measurement of the exposure domain in seven studies [14,[21][22][23][24][25][26]. Lack of consideration for confounders led to a high risk of bias in four studies [24,[27][28][29].…”
Section: Risk Of Bias In the Included Studiesmentioning
confidence: 99%
“…Characteristics of the outbreaks are presented in Tables 2-4. Fifteen studies reported outbreaks caused by bacteria [15-17, 20, 22, 24, 27, 32-39] and 22 studies were outbreaks by viruses [14,18,19,21,23,25,26,[28][29][30][31][40][41][42][43][44][45][46][47][48][49][50]. The largest number of a single pathogen was influenza viruses [40][41][42][43][44][45], followed by group A streptococcus (GAS) [17,20,24,37,38].…”
Section: Characteristics Of the Outbreaksmentioning
confidence: 99%
See 3 more Smart Citations